Transformations in Framing and the Journalistic Production of Peruvian Television Newscasts During the covid-19 Pandemic - Karbaum-Padilla, Gerardo (2023)
As soon as the spread of the covid-19 began, the media’s information production was affected by social distancing restrictions and journalists were exposed health hazards in an attempt to carry out their jobs. This study aims at learning about the transformations undergone by the television newscasts production in Peru, one of the most affected countries by the pandemic at a global level. Qualitative methods were applied through semi-structured interviews with journalists working during the said period, obtaining results that evince the implementation of several devices and unconventional or unsuitable television processes. This issue is cross-sectional through the three audiovisual production stages—namely, pre-production, media coverage, and post-production—a situation that has never taken place so intensely and permanently. All this leads to the conclusion that the newscasts production had to resort to the hybridization of technologies and procedures to continue performing their duties in such an unexpected and complex context.